LEARNING SCIENCE THROUGH ENQUIRY APPROACH FOR AROUSING THE CURIOSITY IN CHILDREN - DOGRA, BHARTI (THE PRIMARY TEACHER, 2013)
Science teaching and learning is traversing the dimensions of analysis, synthesis, inquiry and metacognition. Science teachers across the country need to be able to use these techniques in their classroom pedagogy to provide every student with optimal learning environment. Learning science through inquiry helps students in constructing knowledge through observation, analysis, interpretation, explanation and finally making broader generalisations. The inquiry approach helps in finding answers to questions through investigation where students are treated as ‘scientists in making’. This paper discusses use of inquiry approach in arousing curiosity of children while transacting the science curriculum.